A compact multi‐layer phase correcting lens to improve directive radiation of Vivaldi antenna. Issue 7 (17th April 2017) - Li, Xiangxiang; Liu, Gang; Zhang, Yanmei; Sang, Lei; Lv, Guoqiang
Abstract: Gain of the conventional Vivaldi antenna (CVA) decreases at higher frequencies. A phase correcting lens (PCL) made up of nonresonant rectangular patch unit cells (UCs) is proposed to correct this problem. The layout of the UCs is specially designed taking into account the actual phase error at antenna aperture. The detailed analysis, design and discussion for the CVA with the proposed PCL are performed. The CVA, CVA with one‐layer PCL (CVA‐OPCL), and three‐layer PCL (CVA‐TPCL) are fabricated and measured. The measured results agree well with the simulated ones. The measured results show that the proposed CVA‐TPCL provides a gain variation of 5.75‐14.9 dBi in the wide operating range from 3.5 to 16 GHz, which leads to 1.1‐6.1 dBi gain enhancement than that of the CVA. In addition, the E‐plane half power beamwidths become narrowed significantly at higher frequencies. An average improvement of 4.54 dB is achieved in terms of the front‐to‐back ratio. The sidelobe levels, on average, are reduced by 4.1 dB and 2.8 dB for E‐plane and H‐plane, respectively.